LITERASI DAN HEDONISME TERHADAP PERILAKU KEUANGAN: PERAN INTERVENSI LOCUS OF CONTROL - Kinanti, Kartika Ayu; Chandra, Yulian Ade; Al Maidah, Firdaus; Nareswari, Ayu (Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2025)
Globalization has enhanced economic development worldwide, including in Indonesia. Yet, people increasingly find it difficult to differentiate between wants and actual needs. As financial capacity and education levels grow annually in Indonesia, this study investigates how financial literacy and hedonism impact financial management behavior, with locus of control as a mediating factor. Targeting working women in Jember Regency, the study applied Malhotra's sampling rule, selecting 200 respondents based on 20 indicators. Structural Equation Modeling (SEM) using SmartPLS was employed to analyze the data. Findings reveal that financial literacy and hedonistic tendencies influence financial management behavior, with locus of control playing a significant mediating role.